Question
Ive for \( f \). \( -2=-2(f+2) \) \( f=\square \) Submit
Ask by Estrada Burton. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( f = -1 \)
Solution
Solve the equation \( -2=-2(f+2) \).
Solve the equation by following steps:
- step0: Solve for \(f\):
\(-2=-2\left(f+2\right)\)
- step1: Swap the sides:
\(-2\left(f+2\right)=-2\)
- step2: Change the sign:
\(2\left(f+2\right)=2\)
- step3: Divide both sides:
\(\frac{2\left(f+2\right)}{2}=\frac{2}{2}\)
- step4: Divide the numbers:
\(f+2=1\)
- step5: Move the constant to the right side:
\(f=1-2\)
- step6: Subtract the numbers:
\(f=-1\)
The solution to the equation \( -2=-2(f+2) \) is \( f=-1 \).
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Extra Insights
Let's solve the equation step by step. Starting with the equation, we can first divide both sides by -2, which simplifies to: \( 1 = f + 2 \). Next, we subtract 2 from both sides to isolate \( f \): \( f = 1 - 2 \) which gives us \( f = -1 \). So, the value of \( f \) is \( -1 \).